Panel Kontrol ATS SCADA - Putung, Yoice R.; Sawidin, Sukandar; Kereh, Tracy M.; Langi, Herry S.; Patabo, Muchdar Dg.; Loegimin, Maruto Swatara (JURNAL INTEGRASI, 2024)
To guarantee a steady supply of electricity to the load, the Automatic Transfer Switch (ATS) panel management system is crucial in controlling the power flow between the primary and backup electricity sources. It integrates Supervisory Control and Data Acquisition (SCADA) technologies to improve the effectiveness and dependability of ATS operations. The goal of designing an ATS panel with SCADA control is to establish an ATS panel control system based on SCADA. The SCADA system will handle and evaluate the data gathered from this device in order to track and manage the functioning of the ATS. Additionally, in the event that the primary power source has an interruption or breakdown, the SCADA system will automatically trigger the ATS to switch to a backup source, minimizing recovery time and guaranteeing that the load will always have access to uninterrupted power.